Incidence, outcomes and risk factors of postoperative urinary retention in patients undergoing primary total knee arthroplasty: a national inpatient sample database study - Jing Li; Qiuhong Li; Jianping Zhang; Xianhui Chen; Lin Yang; Yang Zhang; Yuhang Chen (BMC Surgery)
Abstract Background Postoperative urinary retention (POUR) was reported as a common complication in patients undergoing primary total knee arthroplasty (pTKA), but descriptions of its prevalence and negative outcomes vary widely and remain inadequately studied. Methods A retrospective cohort study was conducted using the National Inpatient Sample database from 2005 to 2014. The annual incidence, baseline characteristics, and inpatient outcomes of POUR after pTKA were recorded. Logistic regression analysis was performed to estimate potential predictors of POUR. Statistical significance was defined as P < 0.01. Results A total of 1,228,621 patients undergoing pTKA were identified. The incidence of POUR after pTKA is increasing annually from 2005 (1.51%, 95%CI 1.44-1.59%) to 2014 (2.29%, 95%CI 2.21-2.37%), and the cumulative incidence of POUR was 1.91% (95%CI 1.89-1.93%). POUR was significantly associated with higher Charlson Comorbidity Index and Elixhauser Comorbidity Index scores, and higher medical costs. In patients experiencing pTKA, the Top 5 most significant risk factors for developing POUR were male gender (odds ratio [OR] = 3.40; 95% confidence interval [CI] 3.30–3.51; P < 0.0001), fluid and electrolyte disorders (OR = 2.02; 95% CI 1.94–2.10; P < 0.0001), age over 60 (OR = 1.97; 95% CI 1.89–2.05; P < 0.0001), paralysis (OR = 1.78; 95% CI 1.46–2.17; P < 0.0001), and psychoses (OR = 1.57; 95% CI 1.43–1.72; P < 0.0001). Although POUR did not result in higher inpatient mortality (0.1% vs. 0.07%, P = 0.1242), it may be associated with the occurrence of other complications such as acute myocardial infarction (0.42% vs. 0.20%, P < 0.0001), pulmonary embolism and infarction (0.80% vs. 0.42%, P < 0.0001), acute renal failure (6.06% vs. 1.49%, P < 0.0001), deep venous thrombosis (0.71% vs. 0.45%, P < 0.0001), acute posthemorrhagic anemia (28.89% vs. 19.45%, P < 0.0001), and infection (0.29% vs. 0.15%, P < 0.0001). Conclusions Although POUR has no effect on inpatient mortality, our large-scale national study provides new insights that it increases postoperative complications and impairs clinical outcomes. Given the increasing incidence of POUR, early identification of high-risk patients, particularly those with identified comorbidities, should be prioritized. Preventive strategies, such as optimized perioperative fluid management, may help mitigate the risk of POUR. Future research should focus on developing preventive strategies to mitigate its impact.